Clinical characteristics of recurrent non-arteritic retinal artery occlusion - Se Joon Woo; Hyeong Min Kim (BMJ Open Ophthalmology)
Objectives To investigate the recurrent non-arteritic retinal artery occlusion (RAO) in the same or opposite eye.Methods We searched the RAO registry at Seoul National University Bundang Hospital and included patients with recurrent RAO in the present study. Ophthalmic and systemic features were analysed to identify risk factors and visual outcomes.Results Of the 850 patients in the non-arteritic RAO cohort, 11 (1.3%) experienced a second RAO recurrence, either in the same (5 patients; 0.6%) or opposite (6 patients; 0.7%) eye. The same eye group experienced an earlier recurrence (1–2 months, median 1 month) than the opposite eye group, where the time to recurrence was notably longer (8–66 months, median 22 months). Best corrected visual acuity (BCVA) in the same eye group decreased after the recurrence of RAO. In the same eye group, initial BCVA ranged from 20/200 to counting fingers (CF), while BCVA during RAO recurrence ranged from CF to hand motion. When RAO recurred in the opposite eye, the reduction in visual acuity was less severe than the reduction of the initial episode: initial episode ranged from 20/400 to light perception and recurrent episode ranged from 20/25 to 20/400. Patients exhibited varying degrees of carotid (81.8%) and cerebral (9.1%) artery occlusions. Additionally, one patient in each group (total 2 patients, 18.2%) experienced a stroke 6 months after RAO recurrence.Conclusions Since the RAO recurrences could lead to devastating visual impairment, it is essential to emphasise the importance of risk factor screening to patients while collaborating with neurologists and cardiologists.